Yaron Matras, Anton Tenser (eds.): The Palgrave Handbook of Romani Language and Linguistics: Cham: Palgrave Macmillan, 2020, 596 s., ISBN: 978-3-030-28104-5 - Granqvist, Kimmo (Romano džaniben, 2020)
RECENZE